Ocular manifestation of HIV/AIDS and correlation with CD4+ cells count among adult HIV/AIDS patients in Jimma town, Ethiopia: a cross sectional study - Bekele, Sisay (BioMed Central, 2013)
BACKGROUND: HIV/AIDS is one of twenty first century’s challenges to human being with protean manifestation affecting nearly all organs of our body. It is causing high morbidity and mortality especially in sub-Saharan Africa with numerous ocular complications and blindness. The purpose of this study was to determine the patterns of ocular manifestations of HIV/AIDS and their correlation with CD4+Tcells count. METHODS: A cross-sectional study was done on 348 HIV-positive patients presented to Anti-Retroviral Therapy clinics. Data were collected using face-to-face interview, clinical examination and laboratory investigation, and analyzed using SPSS version 13 software. Statistical association test was done and p<0.05 was considered significant. Other statistical tests like student t-test and logistic regression were also done. RESULTS: Of 348 patients, 175 were on antiretroviral therapy and 173 were not on therapy. The mean duration of therapy was 27 months. The overall prevalence of ocular manifestations was 25.3%. The commonest ocular manifestation was keratoconjunctivitis sicca (11.3%) followed by blepharitis (3.2%), molluscum contagiosum (2.6%), conjunctival squamous cell carcinoma (2.3%), conjunctival microvasculopathy (2.3%), cranial nerve palsies (2%), herpes zoster ophthalmicus (HZO) (1.2%), and HIV retinopathy (0.6%). HIV retinopathy and conjunctival microvasculopathy were common in patient with CD4+ count of <200 cells/μl while HZO and molluscum contagiosum were common in patients with CD4+ count of 200–499 cells/μl. Prevalence of ocular manifestation was higher among patients on HAART (32.6%) than those patients not on HAART (17.9%) (p<0.05). There was statistically significant association between ocular manifestation and sex, CD4+Tcells count, and age (p<0.05). CD4+ count, <200 cells/μl and age >35 years were independent risk factors for ocular manifestations. CONCLUSION: The study showed that the prevalence of ocular manifestation of HIV/AIDS is lower than previous studies and could be due to antiretroviral therapy. Lower CD4 count is a risk as well as predictor for ocular manifestations.